Interventions in school children to decrease body mass index: Literature review - Lizalde Hernández, Azucena (2023)
Objective: To identify the best scientific evidence regarding health interventions to reduce the body mass index in school children with obesity. Method: Literature review based on the PRISMA-2020 statement; selection criteria: quantitative studies, controlled clinical trials and case-control studies; published from 2015 to 2020, Spanish, Portuguese and English languages, free text. Descriptors: (child), (child); (obesity), (obesity); (body mass index), (boby mass index); (schoolchildren), (schoolchildren). Six selected studies with a level of evidence type I and grade of recommendation "A". Main results: Studies applied in primary schools in the United Kingdom, Spain, China and Chile; the primary result was the statistically significant lower BMI after the intervention, 83.3% showed a level of evidence I and grade of recommendation "1A" recommendable for its application in practice. General conclusion: The literature shows a significant decrease in BMI, this decrease is only during the intervention period; the need to develop interventions with long-term follow-up is identified. It is recommended to continue with the analysis and dissemination of the various interventions designed by the scientific community, as well as to favor their inclusion and application within the framework of the health programs of each country.